Microstructural features of lime-stabilised pyroclastic soils. Issue 3 (23rd July 2013) - Russo, G.; Cecconi, M.
Abstract : Some results of an experimental investigation on a lime-stabilised Italian pyroclastic soil are presented and discussed. This material is very reactive with calcium oxide (CaO) provided by the lime, the effectiveness of the stabilisation mainly depending on the amount of low alkali alumino-silicate glass phase. However, there is a lack of systematic studies on the suitability of such pyroclastic soils to lime stabilisation and the effects of treatment parameters on the engineering properties of the stabilised material. The results of laboratory tests (chemical, physical and mechanical) on untreated and lime-stabilised samples allow an overview of the microstructural features of the material and, as a consequence, on the suitability and effectiveness of lime stabilisation.